Meningkatkan Pemahaman Konsep Ipa Melalui Penerapan Metode Demonstrasi Di Kelas Rendah - Agitha Qotrun; Andi Nurochmah; Astri Sutisnawati (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
This study aims to describe an increase in the understanding of the science concept through the application of demonstration methods in the low class. The research method used was Classroom Action Research (CAR) with a research design using the Kemmis and Mc Taggart models which were carried out in two cycles. Each cycle consists of planning, implementation, action and observation, and reflection. The participants in this study were 32 students of class III-B SDN2 Cicurug Sukabumi, consisting of 14 male students and 18 female students. The data collection technique of this study used tests in the form of pretest and posttest. While the non-test technique is in the form of observation, field notes and documentation. The data analysis technique used is quantitative descriptive. In the pre-cycle through the concept understanding test indicators showed completeness of 9% or 3 students who completed. Then increased in the first cycle reached 59% completeness or 19 students completed. While in the second cycle, showed completeness reached 87% or 28 people. students who complete. The overall increase with the calculation of the gain formula scores 0.42 with the medium category. The PTK concluded that understanding the science concept of students in the lower classes increased through the application of demonstration methods.